Leveraging green bonds through green innovation for effective CO₂ mitigation: The moderating roles of institutions, market development and business sophistication - Dao, Nhung Hong; Tran, Thu Thanh; Tran, Tuan Anh (Asian Journal of Economic Modelling, 2025)
The urgent need to improve environmental performance in line with global commitments highlights the critical role of green finance in driving sustainable development. This paper explores the impact of green bonds on greenhouse gas emissions through the mediating role of green innovation. We clarify the effect by collecting and analyzing secondary data from 70 countries from 2012 to 2020 by adopting a country-fixed effects model and a moderated mediation analysis. Empirical results support the hypothesis that green bonds promote environmental quality through the mediating role of green innovation. The findings affirm the significance of sources from green bonds for implementing green innovation. We also validate our findings in different settings with the mediating roles of institutional quality and supporting conditions for innovation at the country level. We found statistical evidence supporting the three proxy variables. Countries with high-quality institutions and strong innovation support can reduce CO2 emissions by utilizing green bonds to conduct green innovation. Our results highlight the importance of green bonds in facilitating green innovation and the role of institutions, markets, and business supporting conditions in reducing CO2 emissions.